Group Problem-Solving Therapy for Postnatal Depression among HIV-Positive and HIV-Negative Mothers in Zimbabwe. (July 2014) - Chibanda, Dixon; Shetty, Avinash K.; Tshimanga, Mufuta; Woelk, Godfrey; Stranix-Chibanda, Lynda; Rusakaniko, Simbarashe
Postnatal depression (PND) is a major problem in low- and middle-income countries (LMICs). A total of 210 postpartum mothers attending primary care urban clinics were screened for PND at 6 weeks postpartum using the Edinburgh Postnatal Depression Scale (EPDS) and Diagnostic and Statistical Manual of Mental Disorders (Fourth Edition; DSM-IV ) criteria for major depression. The HIV prevalence was 14.8%. Of the 210 enrolled postpartum mothers, 64 (33%) met DSM IV criteria for depression. Using trained peer counselors, mothers with PND (n = 58) were randomly assigned to either group problem-solving therapy (PST, n = 30) or amitriptyline (n = 28). Of the 58 mothers with PND, 49 (85%) completed 6 weeks of group PST (n = 27) or pharmacotherapy (n = 22). At baseline, the mean EPDS score for participants randomized to group PST was 17.3 (standard deviation [SD] 3.7), while the group randomized to amitriptyline had a mean EPDS score of 17.9 (SD 3.9; P = .581). At 6 weeks postintervention, the drop in mean EPDS score was greater in the PST group (8.22, SD 3.6) compared to the amitriptyline group (10.7, SD 2.7; P = .0097). Group PST using peer counselors is feasible, acceptable, and more effective compared to pharmacotherapy in the treatment of PND. Group PST could be integrated into maternal and child health clinics and preventing mother-to-child transmission of HIV programs in LMICs.